The Effect Of Kinds Media And Seed Location On Fruit On The Growth Of Moringa (Moringa oleifera Lam) - Nurlianti Pertiwi; Yola Agus Saputra; Prihanani Prihanani; Nurseha Nurseha (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to determine the effect of a mixture of planting media and the location of the seeds on the fruit and their interaction on seed germination and growth of Moringa seedlings. The research was carried out in April – June 2021 in Jalan Gedang sub-district, Gading Cempaka sub-district, Bengkulu city. The altitude of the place is 10-15 meters above sea level. This study was structured using a Completely Randomized Block Design (CRBD) which consisted of 2 treatment factors. The first treatment was a mixture of media (M) with 3 levels, namely M1 which was a mixture of soil: husks (1:1), M2 was a mixture of soil: burnt husks (1:1), M3 was a mixture of soil: manure (1:1). The second factor of the fruit (B) consists of 3 levels of factors, namely B1 which is the base of the seed, B2 is the middle part of the seed. B3 is the end part. The results of the analysis of variance were continued with the Duncan's Multiple Range Test (DMRT) test with a test level of 5%. The results of the study concluded that the mixed media treatment had a significant effect on germination time and root length. In observing the germination time of the mixture of planting media, namely the composition of soil and husks (M1), it was significantly different from the mixture of soil and manure media (M3) but not significantly different from the mixture of soil and burnt husks (M2). The best root lengths, namely M1 and M2 treatments were not significantly different, but both were significantly different from M3. The treatment of seed location and the interaction of types of planting media and seed location on fruit all observed variables had no significant effect.